Troupes of dancers performing in front of the temple - Mumbai Archive Project Team (Jio Institute, 2024)
Troupes of dancers perform in front of the temple as the procession prepares for departure. Cultural programmes featuring music and dance are organized at regular intervals along the route of the procession.